Social Intelligence and Susceptibility to Online Misinformation of Generation Z Learners - Mercer, Lea; Archivido, Maria Luisa (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between social intelligence and Generation Z students’ ability to identify and evaluate misleading online information. Anchored on Social Cognitive Theory, Emotional Intelligence Theory, and Sociocultural Theory, the research investigated whether social intelligence serves as a protective factor against misinformation susceptibility among Junior High School and Senior High School students at Lyceo de Pasacao Inc. A quantitative descriptive-correlational research design was employed involving 102 purposively selected students. Data were collected using adapted versions of the Tromsø Social Intelligence Scale (TSIS) and the Misinformation Susceptibility Test (MIST), which underwent content validation and reliability testing prior to administration. Descriptive and inferential statistical techniques, including correlation analysis, were used to analyze the data. The findings revealed that respondents demonstrated a high level of social intelligence in terms of social information processing, social skills, and social awareness. However, they exhibited mixed susceptibility to online misinformation and manipulation. Students performed best in recognizing credible and institutional sources but showed greater vulnerability to emotional manipulation, sensationalism, conspiracy-related content, health misinformation, and repeated unsupported claims. Correlation analysis indicated weak negative and statistically insignificant relationships between all dimensions of social intelligence and misinformation susceptibility, leading to the retention of the null hypothesis. The results suggest that social intelligence alone is insufficient to predict students’ ability to identify and evaluate misleading online information. Consequently, the study recommends the implementation of a Digital Social Intelligence and Media Literacy Program that integrates media literacy, critical thinking, fact-checking, emotional regulation, and digital resilience. The study aligns with SDG 4 (Quality Education) by promoting media literacy, critical thinking, and informed decision-making, and with SDG 16 (Peace, Justice and Strong Institutions) by supporting responsible information consumption and resistance to misinformation. Its sustainability contribution lies in strengthening educational, community, and digital resilience through the development of informed, responsible, and critically engaged digital citizens.